Underweight and associated factors among children under age of five in low and lower-middle income African countries: hierarchical analysis of demographic and health survey data - Tamir, Tadesse Tarik; Zegeye, Alebachew Ferede; Workneh, Belayneh Shetie; Mekonen, Enyew Getaneh (Frontiers in Public Health, 2024)
Introduction Globally, nearly half of all deaths among children under the age of five are linked to undernutrition. These tragic outcomes are most prevalent in low- and middle-income countries. The far-reaching impact of malnutrition affects not only individuals but also their families, communities, and entire nations. By examining underweight, we gain valuable insights into the intricate network of factors influencing child health. Therefore, this study aims to assess underweight prevalence and its associated factors among under-five children in low and lower-middle-income African countries. Method We conducted a secondary analysis of standard demographic and health surveys in 30 low and lower-middle-income African countries spanning from 2012 to 2022. Our analysis included a total sample of 200,655 children under the age of 5 years. We employed a three-level hierarchical model to assess the determinants of underweight among children in this age group. Measures of association were evaluated using adjusted odds ratios with a 95% confidence interval. Explanatory variables with a p-value less than the level of significance (0.05) were considered statistically significant. Result The pooled prevalence of underweight among children under the age of five in low and lower-middle income African countries was estimated at 17.60%, with a 95% confidence interval (CI) ranging from 17.44 to 17.77%. The hierarchical analysis identified several factors significantly associated with underweight, including male gender, birth size, maternal body mass index, maternal educational level, household wealth index, antenatal care (ANC) visits, community poverty level, and income level of countries. Conclusion The high prevalence of underweight among children under the age of five in low and lower-middle income African countries underscores the need for targeted interventions. By addressing individual, community, and country-level factors, we can work toward improving child nutrition and well-being.